Power Sector Development in Myanmar - Kee-Yung Nam; Maria Rowena Cham; Paulo Rodelio Halili (Asian Development Bank (ADB), 2015)
While the economic literature has yet to establish whether greater electricity consumption leads to faster economic growth, or vice versa, it is widely accepted that the better provision of electricity can enable pro-poor growth. Because electricity consumption is expected to grow in emerging economies such as Myanmar, it is important that the government prioritize its stable, efficient, and affordable supply. This paper assesses Myanmar's electricity sector and recommends several concrete policy options to enable government to address issues such as supply security, greater accessibility, and affordability, especially for the poor and disadvantaged. The paper also estimates infrastructure demand and the corresponding investment requirements to narrow the supply gap in the power sector.
hdl:11540/5248
Keywords: H54; L94; Q43; Q47; 330; electricity access; Myanmar; power investment gap; power sector development; supply security